Agricultural poverty in Panama for Asian perspective - Tang, Anthony M. (1988)
The paper offers an Asia frame of reference to the technological and institutional dualism within agriculture in Panama and its role in defining the character of Panamanian rural poverty. Firstly, it draws up a profile of poverty farms which corroborates the descriptive profile yielded by a study conducted by the Panamanian government. Next, it outlines the the economics of under development and then proceeds to an extensive discussion of the development of poverty theories, particularly with reference to agriculture. It then presents a regression model based on the relationships hypothesized in the theoretical formulations, and using 1970 farm data for each of Panama's 66 Districts. Based on the regression results showing that Panamian farmers of all sizes are responsive to economic opportunities, the paper recommends the abandonment of high selective price support and of government import monopoly by IMA in favor of world market prices. Taking into consideration the crucial importance of locational variables as determinants of farm income, the paper further proposes a homestead land redistribution program by making all public farmlands available for permanent settlement by farm households. This would serve to reconcentrate farm settlements in areas with more favorable locational characteristics. Finally, to complement the price and land reform measures, it is suggested that multi-purpose cooperatives be established, like the Farmers' Association of East Asia.
Keywords: Panama -- Literary collections; Poverty -- Economic aspects; Panama -- Agriculture